Plant density influence on life history traits of a perennial herb in rocky outcrops, southeastern Brazil - Demetrio, Guilherme Ramos; Barbosa, Mario Eduardo Avelar; Coelho, Flávia de Freitas (Iheringia, Série Botânica., 2020)
Rocky outcrops support a great diversity of edaphic conditions and associated vegetation mosaics greatly determined by factors like local topography and micro-environment. The vegetation is grouped, and clonal plants may form patches with different densities. Densitydependent responses are an important component of organism’s life-histories. We evaluated the density effects on Vellozia albiflora traits. We settled 20 monospecific patches of V. albiflora with different densities and sampled vegetative and reproductive traits. We compared traits between plants experimenting densely crowded and uncrowded conditions. V. albiflora rosettes present larger sizes and higher production of sexual reproductive structures in high densities. We concluded that V. albiflora probably allocates more resources to sexual reproduction in response to high-density conditions, which may allow a higher survival of offspring, since seeds are able to endure in soil and germinate under better density conditions, whereas the propagules generated by asexual reproduction must establish right after their production.